Locating bluetooth devices through an android application by creating an ad hoc network - Pamboukas, Savvas (2014)
The significant evolution of mobile software and hardware led the world from Bill Gate's vision "a PC in every house" to the era “a PC in every pocket". The features of today's phones combined with the low prices of internet accessibility allow the users to be online everywhere and that brought tied consequences in every aspect of our life. The new generation of developers; mobile application developers, flood the market with programs which its variety shows how far the creativity of a human can reach. Nowadays phones are equipped with Wi-Fi, 3G, Bluetooth, NFC and numerous other components. Thus we can easily find and communicate with a person through the Internet using 3G (or 4G) or Wi-Fi. But what happens with other objects? Can we find the location of essential lost objects like a wallet, our keys or even a lost little child (little enough who don't have a mobile phone) through a mobile application? That's the problem this dissertation is going to solve in a cheap and efficient way with the development of Bluetooth Finder android application. We propose an android application the Bluetooth Finder. It discovers Bluetooth devices and stores their location on the cloud. The user of Bluetooth Finder app has the option to search in this database by pressing a button in case a bonded Bluetooth object or maybe a person attached with a BT tag is missing. For our scope any Bluetooth device is applicable and we can make any object BT aware since we can attach a BT tag device on it. An advantage of mobile phones is that their owners are moving arbitrary, giving us the opportunity to use them as nodes in an ad hoc network. Thus, people with their android devices can be used as a "searching devices" and update the location of any BT device found in their way. The locations of the devices are saved on the cloud as latitude and longitude. The possibility of the user not be on the Internet is covered since the BT devices discovered are saved on the phone's memory until the user gets online. Then the new data are automatically uploaded on the cloud. We also testing Bluetooth Finder in a real Android device and we provide the results and the cloud database created.